Synthesis of arylmethylureas and the influence of structure on their antispasmodic activity; Pharmaceutical Chemistry Journal; Vol. 25, iss. 5 - Filimonov V. D. Viktor Dmitrievich; Bakibaev A. A. Abdigali Abdimanapovich; Tignibidina L. G.; Gorshkova V. K.; Saratikov A. S.; Pustovoitov A. V.; Dobychiha N. S.; Pechenkin A. G. (1991, 1991)
Title screen